2018
DOI: 10.3390/s18072188
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Vehicle Roll Angle Estimation Based on Neural Networks in IoT Low-Cost Devices

Abstract: The high rate of vehicle-crash victims has a fatal economic and social impact in today’s societies. In particular, road crashes where heavy vehicles are involved cause more severe damage because they are prone to rollover. For this reason, many researches are focused on developing RSC Roll Stability Control (RSC) systems. Concerning the design of RSC systems with an adequate performance, it is mandatory to know the dynamics of the vehicle. The main problem arises from the lack of ability to directly capture se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…First, the IoT-based sensor device developed in this study is based on Raspberry Pi which is small-size, low-cost, and powerful single-board computer device. Previous studies have shown significant advantages of utilizing Raspberry Pi such as for controlling and monitoring IoT system [ 83 ], estimating the roll angle of a vehicle using embedded neural network in real-time [ 84 ], hosting and serving the user interface of eHealth care system [ 59 ], and monitoring the temperature of lava lake using near infrared thermal camera [ 85 ]. Therefore, the proposed IoT-based sensor device developed in this study could be applied to monitor the manufacturing process in real-time.…”
Section: Resultsmentioning
confidence: 99%
“…First, the IoT-based sensor device developed in this study is based on Raspberry Pi which is small-size, low-cost, and powerful single-board computer device. Previous studies have shown significant advantages of utilizing Raspberry Pi such as for controlling and monitoring IoT system [ 83 ], estimating the roll angle of a vehicle using embedded neural network in real-time [ 84 ], hosting and serving the user interface of eHealth care system [ 59 ], and monitoring the temperature of lava lake using near infrared thermal camera [ 85 ]. Therefore, the proposed IoT-based sensor device developed in this study could be applied to monitor the manufacturing process in real-time.…”
Section: Resultsmentioning
confidence: 99%
“…Given its suitability for applications in many areas, the RPi has been used in a large number of research projects, from sensor networks [ 4 , 5 , 6 ], vehicle active safety systems [ 7 ], e-health care [ 8 ], big data analytics [ 9 ], and image analysis [ 10 ], to various other areas. It has also been widely used in educational projects [ 11 ], and in the construction of affordable and energy-efficient clusters consisting of up to 300 nodes [ 12 ], which partially offsets its lack of computing power.…”
Section: Introductionmentioning
confidence: 99%
“…To predict the lateral load transfer and roll stability vector in roll stability control system, the NN-based roll angle estimations in [148,149,150] were taken into account using IoT low-cost devices and IMU where longitudinal and lateral accelerometer, yaw rate, and roll rate can be easily measured as training set, and the NN embedded in IoT low-cost devices can handle real-time constraints. Herein, the experimental result verified that the NN can obtain improved accuracy during the estimating process of vehicle roll angle with respect to KF [150].…”
Section: Data-driven-based Vehicle Estimationmentioning
confidence: 99%